Experience of Nursing students with debriefing in high-fidelity clinical simulation (Research, Society and Development, 2024)
Simulation is a teaching methodology with long-term knowledge acquisition from simulated or real experiences, debriefing is a reflection and evaluation component of this process and the teacher is the main figure. This study aimed to evaluate the experience of nursing students with debriefing after clinical simulation as a teaching strategy. This is a quantitative, cross-sectional study carried out from the development of a workshop entitled "Nursing care for patients with wounds", it was applied a dialogued class about the theoretical content, after that, the student was referred to laboratory activities where the simulation happened with a simulated patient, following a theoretical reference. After the scenario resolution, the debriefing was carried out. The study included 53 nursing students from the 6th, 7th, 8th terms. As for the results, it was possible to identify, from the application of 2 scales and the Student's Test, that the students who showed greater satisfaction with the simulated clinical experience were those in the 8th term, whereas those in the 6th term showed greater satisfaction and self-confidence. To verify the hypothesis “Realistic simulation is a pedagogical tool that depends on the teacher”, the Student's Test presented p